2022
DOI: 10.1155/2022/4989248
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Environmental and Geographical (EG) Image Classification Using FLIM and CNN Algorithms

Abstract: Intelligent machines have grown in importance in recent years in object recognition in terms of their ability to envision, comprehend, and reach decisions. There are a lot of complicated algorithms that accomplish AI utilities. In addition to their use in the medical industry, these methods of object recognition have a wide range of other fields, most notably industries, in which they can be applied. In contrast to the proposed calculation, the proposed calculation is less complex and more accurate under certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Technical innovation: Cloud service platform for fertilizer distribution in agricultural greenhouse irrigation [16][17][18]. Cloud service platform for fertilizer distribution in agricultural greenhouse based on Internet of Things and agricultural big data, making full use of the advantages of information technology, to achieve accurate management and instant service in the whole process of fertilizer distribution; The model of liquid microbial soil remediation agent enables the software system of fertilizer dispenser to give the best dosage and application method of liquid microbial soil remediation agent according to soil parameters, crop parameters and fertilizer allocation parameters, so as to realize equal emphasis on chemical fertilizer reduction and soil remediation and sustainable development of land.…”
Section: Voice Control Modementioning
confidence: 99%
“…Technical innovation: Cloud service platform for fertilizer distribution in agricultural greenhouse irrigation [16][17][18]. Cloud service platform for fertilizer distribution in agricultural greenhouse based on Internet of Things and agricultural big data, making full use of the advantages of information technology, to achieve accurate management and instant service in the whole process of fertilizer distribution; The model of liquid microbial soil remediation agent enables the software system of fertilizer dispenser to give the best dosage and application method of liquid microbial soil remediation agent according to soil parameters, crop parameters and fertilizer allocation parameters, so as to realize equal emphasis on chemical fertilizer reduction and soil remediation and sustainable development of land.…”
Section: Voice Control Modementioning
confidence: 99%
“…The average results demonstrate that the created controller can automatically and effectively regulate blood glucose levels for simulations lasting up to 12 hours and incorporating two meals. It is feasible to look into this exploratory work further [2].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%